The Empire's New Clothes Cultural Particularism and Universal Value in China's Quest for Global Status - Paltiel, J.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2007)
This book assesses the challenge to the dominance of Euro-American political and economic liberalism from China's emergence as a global presence. China presents the most significant present-day example of the dual process of participation and resistance. Paltiel's offers intriguing insights into the prospect of equality in a system of global power.
Keywords: Ethnology—Asia.; Asia—Politics and government; International relations; China—History.; Asian Culture; Asian Politics; International Relations; History of China